2020
DOI: 10.1103/physrevmaterials.4.044402
|View full text |Cite
|
Sign up to set email alerts
|

Interface-related magnetic and vibrational properties in Fe/MgO heterostructures from nuclear resonant spectroscopy and first-principles calculations

Abstract: We combine 57 Fe MÃűssbauer spectroscopy and 57 Fe nuclear resonant inelastic x-ray scattering (NRIXS) in nanoscale polycrystalline [bcc-57 Fe/MgO] multilayers with various Fe layer thicknesses and layer-resolved density-functional-theory (DFT) based first-principles calculations of a (001)-oriented [Fe(8 ML)/MgO(8 ML)](001) heterostructure to unravel the interface-related atomic vibrational properties of a multilayer system. In theory and experiment, we observe consistently enhanced hyperfine magnetic fields … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…The obtained depth profiles show interfacial enhancement of the Fe orbital and spin magnetic moments at the Fe/MgO interface. This enhancement is consistent with findings of previous theoretical studies. By contrast, the spin magnetic moment diminished at the Fe/V interface. This decrease may balance the increase at the Fe/MgO interface and result in a nominally absent magnetic dead layer (Figure e).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained depth profiles show interfacial enhancement of the Fe orbital and spin magnetic moments at the Fe/MgO interface. This enhancement is consistent with findings of previous theoretical studies. By contrast, the spin magnetic moment diminished at the Fe/V interface. This decrease may balance the increase at the Fe/MgO interface and result in a nominally absent magnetic dead layer (Figure e).…”
Section: Resultssupporting
confidence: 93%
“…It was theoretically predicted that the Fe spin and orbital magnetic moments increase when interfaced with MgO. Experimentally, Miyokawa et al and Sicot et al observed such enhancements in a 1–2-monolayer (ML) thick Fe sandwiched between MgO and Co layers by performing X-ray magnetic circular dichroism (XMCD) measurements, , although the authors recognized that the Co underlayer most likely affected the magnetic properties of such a thin Fe layer. Jal et al showed that the magnetic moments increased by 24% in a 2–3-ML thick Fe next to an interface in an MgO/Fe (12 nm)/MgO heterostructure .…”
Section: Introductionmentioning
confidence: 99%
“…The Fe/MgO system was extensively investigated in the context of TMR (tunnel mag- netoresistance) and benefits from the fact that electronic, magnetic and transport properties are well established [40,41,[43][44][45][46][47][48][49][50]. Recently, also optical and lattice excitations have been subject to theoretical and experimental studies [36,42,51,52]. Bulk Fe is a ferromagnetic metal with bcc structure and a magnetic moment of 2.22 µ B /atom [53], showing a substantial density of occupied and unoccupied d-states in the vicinity of the Fermi level.…”
Section: Introductionmentioning
confidence: 99%
“…In epitaxial thin lms and superlattices, the broken translational symmetry at the surface and interface constitutes a source of novel vibration dynamics, which relaxes towards the bulk behavior within a few atomic layers. [28][29][30][31][32][33][34][35][36][37][38] In amorphous thin lms, the structural disorder induces a reduction and a broad distribution of the mean force constants, leading to a signicant enhancement of the number of lowenergy states. [39][40][41] Fundamentally, the origin of the high-k property is directly related to the vibrational spectrum of a solid, since the static dielectric constant is a sum of the electronic and lattice contributions.…”
mentioning
confidence: 99%